2015
DOI: 10.3892/mmr.2015.3602
|View full text |Cite
|
Sign up to set email alerts
|

Acylglycerol kinase promotes the proliferation and cell cycle progression of oral squamous cell carcinoma

Abstract: Abstract. Cell proliferation is a major underlying cause of mortality amongst patients with oral squamous cell carcinoma (OSCC); however, the underlying mechanisms have remained to be elucidated. Acylglycerol kinase (AGK) is a multisubstrate lipid kinase, which is known to be associated with the progression of various types of human cancer. The present study aimed to investigate the role of AGK in cell proliferation and cell cycle progression in OSCC. The expression levels of AGK were detected in cancerous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Therefore, further investigation of the mechanism is of great value for RCC treatment. A previous study demonstrated that AGK can regulate the cell cycle of oral squamous cell carcinoma cells [16]. Wang et al found that AGK can activate the PI3K/AKT signalling pathway and then inhibit cell cycle inhibitors in breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, further investigation of the mechanism is of great value for RCC treatment. A previous study demonstrated that AGK can regulate the cell cycle of oral squamous cell carcinoma cells [16]. Wang et al found that AGK can activate the PI3K/AKT signalling pathway and then inhibit cell cycle inhibitors in breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…Bektas et al confirmed that upregulation of LPA expression can increase its binding to epidermal growth factor receptor (EGFR), which changes the cytoskeletal structure, induces cell formation and promotes the metastasis of prostate cancer [10]. In addition, numerous studies have demonstrated that AGK is a powerful oncogene [11][12][13][14][15][16][17]. High expression of AGK can induce the expression of hypoxia-inducible factor 1a (HIF1a) and promote epithelial-mesenchymal transition (EMT) in cervical squamous carcinoma cells [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cycle regulation occurs mainly via two key limiting points, G1/S and G2/M (7). The main regulation factors at the G2/M phase include cyclin B, cyclin-dependent kinase 1, also termed cell division cycle (Cdc) 2, cyclin-dependent kinase 2 and Cdc25C (8).…”
Section: Introductionmentioning
confidence: 99%
“…By acting as a lipid kinase, AGK catalyzes the phosphorylation of acylglycerol to generate lysophosphatidic acid (LPA) [ 8 11 ], which is known to be involved in tumor progression [ 12 ], invasion, neovascularization, and metastasis [ 13 ]. AGK was reported to be overexpressed in prostate, breast, esophageal squamous cell carcinoma (ESCC), and oral squamous cell carcinoma [ 8 , 14 17 ]. Bektas et al demonstrated that overexpression of AGK enhanced the proliferation and migration of prostate cancer cells in vitro [ 8 ].…”
Section: Introductionmentioning
confidence: 99%